2010
DOI: 10.1007/s10802-010-9392-3
|View full text |Cite
|
Sign up to set email alerts
|

Personality Mediation of Genetic Effects on Attention-Deficit/Hyperactivity Disorder

Abstract: Personality traits may be viable candidates for mediators of the relationship between genetic risk and ADHD. Participants were 578 children (331 boys; 320 children with ADHD) between the ages of six and 18. Parents and teachers completed a comprehensive, multistage diagnostic procedure to assess ADHD and comorbid disorders. Mother completed the California Q-Sort to assess child Big Five personality traits. Children provided buccal samples of DNA which were assayed for selected markers on DRD4, DAT1, and ADRA2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…Further, past work has indicated that the topics of inter-parental disputes are differentially related to children’s reactions and behaviors, such that conflict regarding the child is linked to greater behavioral dysregulation than are other sources of inter-parental conflict (e.g., financial concerns, Cummings & Davies, 2002). Theoretically, self-blame associated with inter-parental conflict seems to predispose children to adopt a negative interpersonal style that then characterizes their interactions with others and may increase dispositional traits like neuroticism (Martel et al, 2010; Lengua, 2005; Pergamin-Hight, Bakersman-Kranenburg, van IJzendoorn, & Bar-Haim, in press). High neuroticism may, in turn, increase risk for the later development of ODD (Stringaris & Goodman, 2009; Tackett, 2006; Watson et al, 2006), serving as a useful early developmental phenotype of the disorder (Martel, 2009; Sonuga-Barke & Halperin, 2011).…”
Section: Theoretically-driven Multi-level Pathways For Odd and Adhdmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, past work has indicated that the topics of inter-parental disputes are differentially related to children’s reactions and behaviors, such that conflict regarding the child is linked to greater behavioral dysregulation than are other sources of inter-parental conflict (e.g., financial concerns, Cummings & Davies, 2002). Theoretically, self-blame associated with inter-parental conflict seems to predispose children to adopt a negative interpersonal style that then characterizes their interactions with others and may increase dispositional traits like neuroticism (Martel et al, 2010; Lengua, 2005; Pergamin-Hight, Bakersman-Kranenburg, van IJzendoorn, & Bar-Haim, in press). High neuroticism may, in turn, increase risk for the later development of ODD (Stringaris & Goodman, 2009; Tackett, 2006; Watson et al, 2006), serving as a useful early developmental phenotype of the disorder (Martel, 2009; Sonuga-Barke & Halperin, 2011).…”
Section: Theoretically-driven Multi-level Pathways For Odd and Adhdmentioning
confidence: 99%
“…Recent research and meta-analysis suggests that consistency of parenting may moderate the relationship between DRD4 and ADHD such that homozygosity for the DRD4 promoter 120-bp tandem repeat insertion allele increases vulnerability for ADHD and ODD only in the presence of inconsistent parenting (Nigg, Nikolas, & Burt, 2010; Martel et al, 2010; Sonuga-Barke et al, 2009). Further, child traits like low conscientiousness are influenced by parenting (Lengua, 2005; van den Akker et al, 2010), have been associated with ADHD (Martel & Nigg, 2006; Parker, Majeski, & Collin, 2004), and mediate genetic influences on ADHD (Martel et al, 2010), suggesting that they may be useful developmental phenotypes of the disorder (Sonuga-Barke & Halperin, 2010). Thus, genes influencing dopaminergic neurotransmission may interact with negative environmental socialization influences such as inconsistent parenting that would then lead to decreases in childrens’ conscientiousness which, in turn, leads to the manifestation of ADHD symptomatology.…”
Section: Theoretically-driven Multi-level Pathways For Odd and Adhdmentioning
confidence: 99%
See 3 more Smart Citations